Effects of Active and Passive Control Techniques on Mach 1.5 Cavity Flow Dynamics - Selin Aradag; Kubra Asena Gelisli; Elcin Ceren Yaldir (International Journal of Aerospace Engineering)
Supersonic flow over cavities has been of interest since 1960s because cavities represent the bomb bays of aircraft. The flow is transient, turbulent, and complicated. Pressure fluctuations inside the cavity can impede successful weapon release. The objective of this study is to use active and passive control methods on supersonic cavity flow numerically to decrease or eliminate pressure oscillations. Jet blowing at several locations on the front and aft walls of the cavity configuration is used as an active control method. Several techniques are used for passive control including using a cover plate to separate the flow dynamics inside and outside of the cavity, trailing edge wall modifications, such as inclination of the trailing edge, and providing curvature to the trailing edge wall. The results of active and passive control techniques are compared with the baseline case in terms of pressure fluctuations, sound pressure levels at the leading edge, trailing edge walls, and cavity floor and in terms of formation of the flow structures and the results are presented. It is observed from the results that modification of the trailing edge wall is the most effective of the control methods tested leading to up to 40 dB reductions in cavity tones.